Singular 1-soliton and Periodic Solutions to the Nonlinear Fisher-Type Equation with Time-Dependent Coefficients. (1st April 2016) - Guner, Ozkan; Bekir, Ahmet
Abstract: In this article, we establish exact solutions for the variable-coefficient Fisher-type equation. The solutions are obtained by the modified sine-cosine method and ansatz method. The soliton and periodic solutions and topological as well as the singular 1-soliton solution are obtained with the aid of the ansatz method. These solutions are important for the explanation of some practical physical problems. The obtained results show that these methods provide a powerful mathematical tool for solving nonlinear equations with variable coefficients.